2017
DOI: 10.1093/mnras/stx2128
|View full text |Cite
|
Sign up to set email alerts
|

Discussing the distance bias in the estimation of Hi-GAL compact source physical properties – II. Evolutionary status and star formation rate

Abstract: The derivation of the evolutionary stage and rate of star formation of star-forming sites from Galactic single-dish far-infrared and submillimetre surveys suffers from the relatively limited spatial resolution that prevents access to 'core' scales (r ≤ 0.1 pc) for heliocentric distances d 1 kpc. In a previous article, we studied the implications of this 'distance bias' for the mass-radius relationship and its ability to diagnose potential sites for high-mass star formation, using a method that simulates the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…This effect will tend to cause the observed slopes to be shallower, if more luminous, typically more distant, sources tend to have more contamination from surrounding clump material. However, Baldeschi et al (2017) found that increasing distance, although causing source positions to shift in the L − M diagram, does not change the slope, on average. In addition, the luminosity used in this diagram is the true total luminosity from the source, which may differ from the luminosity directly integrated from the SEDs by an order of magnitude or more depending on the viewing inclination, since more radiation is emitted in the polar direction due to low density outflow cavities (see §2.3.3).…”
Section: Parameter Spacementioning
confidence: 86%
“…This effect will tend to cause the observed slopes to be shallower, if more luminous, typically more distant, sources tend to have more contamination from surrounding clump material. However, Baldeschi et al (2017) found that increasing distance, although causing source positions to shift in the L − M diagram, does not change the slope, on average. In addition, the luminosity used in this diagram is the true total luminosity from the source, which may differ from the luminosity directly integrated from the SEDs by an order of magnitude or more depending on the viewing inclination, since more radiation is emitted in the polar direction due to low density outflow cavities (see §2.3.3).…”
Section: Parameter Spacementioning
confidence: 86%
“…We stress that the column density of a structure can depend upon its size. For example, if the size of a structure (a clump, a core, a filament) is smaller than 18 , then this structure is smoothed out in our maps and its peak column density is underestimated; this effect can be important for distant regions 1 (see also discussions in Baldeschi et al 2017).…”
Section: Creation Of Dust Temperature and Column Density Mapsmentioning
confidence: 96%
“…In short, the contribution of each protostellar source to the total SFR is computed through theoretical evolutionary tracks reported in the bolometric luminosity versus mass diagram (Molinari et al 2008;Baldeschi et al 2017b;Elia et al 2021). At each time step, together with the clump mass-luminosity pair, the mass of the internal protostar being formed is also computed.…”
Section: Computation Of the Star Formation Ratementioning
confidence: 99%
“…Baldeschi et al (2017a) proposed a method to evaluate this possible bias by simulating the appearance of nearby star-forming regions observed by the Herschel Gould Belt Survey (André et al 2010) if they were moved to larger distances (from 0.75 to 7 kpc), comparable to those typically found in the Hi-GAL survey. Subsequently, in Baldeschi et al (2017b) this approach was applied, in particular, to the estimation of the SFR. For three nearby regions they compared the SFR obtained from YSO counts (based on an updated version of Equation (1) of Lada et al 2010) to that estimated through the method of Veneziani et al (2017) from the clumps detected in the Herschel maps "displaced" at different virtual distances.…”
Section: Computation Of the Star Formation Ratementioning
confidence: 99%